Implementing Project Based Learning to Increase The Quality of Students’ Statements on Procedural Dimension on Ecosystem Chapter in Grade X IPS 2 SMA N 3 Surakarta - Nanik Murti Prasetyanti; Denny Muhammad Fajar; Joko Ariyanto (Universitas Sebelas Maret, 2015)
The aim of this research was to increase the quality of students’ statements on procedural dimension through Project Based Learning in grade X IPS 2 SMA N 3 Surakarta academic year 2014/2015 on ecosystem chapter. This research was class action research in two cycles each. The primary data was taken through direct observation, meanwhile the secondary data was taken through interviews and documentation. The data was validated through triangulation method and analyzed through qualitative descriptive. The students’ statements were transcripted then grouped in dimension of knowledge on factual, conceptual, procedural and metacognition. The statements on procedural dimension were categorized based on order thinking skill of Bloom’s Taxonomy revised then counted in each order. The statements on factual, conceptual and metacognition dimension was used as supplemental data. The results of this research were: 1) the implementation of PJBL increased the quality of students’ statements on procedural dimension 2) increasing on the quality of students’ statements on procedural dimension were observed in each cycle 3) the quantity of students’ statements on procedural dimension in the pre-cycle was 22, which were 19 statements on procedural C1 and 3 statements on procedural C2, in the first cycle was 60, which were 18 statements on procedural C1, 19 statements on procedural C2, 2 statements on procedural C4, 14 statements on procedural C5 and 7 statements on procedural C6, in the second cycle was 94, which were 23 statements on procedural C1, 19 statements on procedural C2, 2 statements on procedural C5 and 50 statements on procedural C6..Keywords: students’ statements, project based learning